Decreased serum transforming growth factor‐β1 concentration with aging is associated with the severity of emphysema in chronic obstructive pulmonary disease. Issue 4 (26th February 2013) - Kamio, Koichiro; Ishii, Takeo; Motegi, Takashi; Hattori, Kumiko; Kusunoki, Yuji; Azuma, Arata; Gemma, Akihiko; Kida, Kozui
<x xml:space="preserve">Abstract</x> Aim Age‐associated changes of the lung might increase pathogenetic susceptibility to chronic obstructive pulmonary disease (COPD). Decrement in serum transforming growth factor (TGF)‐β1 concentration is reported in elderly people. As impaired TGF‐β1 signaling could cause emphysema‐like changes, we hypothesized that decreased TGF‐β1 with aging is correlated with emphysema. Methods Symptomatic patients with or without COPD and healthy normal subjects without COPD were recruited (COPD, n = 182; smoking controls, n = 73; normal, n = 26). We investigated the correlation between TGF‐β1 and extent of emphysema and airway wall thickness, which were defined as the percentage of low‐attenuation area (LAA%) and large airway wall area (WA%) on pulmonary high‐resolution computed tomography, respectively. The correlation of pulmonary function test parameters and TGF‐β1 was evaluated. TGF‐β1 was determined by enzyme‐linked immunosorbent assay. Results TGF‐β1 significantly decreased with age (P = 0.0009). When the correlation between age and TGF‐β1 was analyzed in each group, a significant inverse correlation was found in COPD patients and smoking controls (P = 0.0095 and 0.0132, respectively), whereas no correlation was observed in healthy older adults. Among COPD patients with severe emphysema, LAA% was inversely correlated with TGF‐β1 (n = 89, P = 0.0104), whereas WA% and pulmonary function test parameters were not. Conclusions Although no correlation was found between TGF‐β1 and the severity of COPD, TGF‐β1 significantly decreased as emphysema became more severe. Age‐related decrease of TGF‐β1 in COPD might be associated with emphysematous alterations of the lungs in elderly subjects. Geriatr Gerontol Int 2013; 13: 1069–1075.